Multi-level governance in the protection of the fundamental right to the environment in the European Union: the European Ecological Pact and the Cities Mission project - MOREIRA, Fátima Castro; Pereira MATOS, André (Revista Jurídica Portucalense, 2022)
The European Union, as a sui generis entity, seeks to deal with global threats and to contribute to their resolution or mitigation. However, it has tried to exercise this agency through strategic alternatives with the aim of outlining innovative ways of conceiving the exercise of authority and power, without jeopardizing the legitimacy of the process, namely through multilevel governance, as a way of enhancing more effective policies and norms before the challenges of this century – such as climate change. Thus, the present article intends to test the less studied articulation of governance between the supra-state and subnational levels in the domain of a transnational public good of special urgency, which is that of environmental protection. To this end, the following research question arises: in what way and with what results does the European Union apply a multilevel governance strategy to foster the protection against climate change, in articulation with the state and subnational levels? The action of the European Union, namely within the scope of the Cities Mission Project, constitutes the selected case study, to which normative analysis and literature review are added, in an inductive approach that intends to appreciate the operationalization of multilevel governance by this supranational institution.